Multiple Impact of Individual Value Systems, Facets of Job Satisfaction, And Organizational Climate Upon the Commitment of Boarding School Teachers in South Tapanuli Regency - Rohman, Fatkhur; Wijaya, Candra; Mesiono, Mesiono (Sekolah Tinggi Agama Islam Al Hidayah, 2022)
This study's objectives were to confirm that personality traits including conscientiousness and agreeableness as well as job satisfaction and organizational climate as environmental factors influence organizational commitment and to compare the organizational commitment of Islamic boarding schools teachers in the South Tapanuli Regency. A questionnaire was utilized to collect data from 157 teachers, taken by consulting the Krejcle-Morgan, as a study instrument. Using descriptive statistics and path analysis, the impacts of conscientiousness, agreeableness, job satisfaction, and organizational climate on organizational commitment were investigated. Path analysis is initiated by carrying out a requirements analysis test including the normality test, linearity test and regression significance, data homogeneity test, independence test between exogenous variables, and correlation test between variables. According to the findings of the study, there is a direct effect of conscientious on teacher job satisfaction with a path coefficient of 0.066, the direct effect of agreeableness on job satisfaction with a path coefficient of 0.098, the direct effect of organizational climate on teacher job satisfaction with path coefficient of 0.032, conscientious direct effect on teacher commitment with a path coefficient of 0.041, a direct effect agreeableness to teacher commitment with a path coefficient of 0.064, the direct effect of organizational climate on teacher commitment with a coefficient path of 0.053, conscientious indirect effect on commitment teachers through job satisfaction with a path coefficient of 0.021, no effect direct agreeableness to teacher commitment through job satisfaction with path coefficient of 0.022, the indirect effect of organizational climate on teacher commitment through job satisfaction with a path coefficient of 0.025 and there is a direct effect of job satisfaction on teacher commitment with a coefficient line of 0.081.